ASB ANALISIS STANDAR BELANJA UNTUK PENYUSUNAN RKA-APBD KEGIATAN PENYELENGGARAAN RAPAT - Meilinda Trisilia (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) STIE Tri Dharma Nusantara, 2020)
The preparation and management of regional budgets are required to be more realistic and transparent. In the digital era, through e-government programs, it is expected to increase transparency, control, and accountability of government administration in order to implement Good Governance in kkn-free government. The preparation of ASB will help local financial management to be more transparent, fair, accountable and the efficiency of local government budgets can be achieved. The preparation of this ASB aims to establish an ASB model of Meeting activities within the Office and outside the Office that is used to assess the fairness of the workload and cost of such activities. This research uses descriptive research and in data analysis using Ordinary Least Square (OLS) method. This research produces a viable ASB model so that it can be used as a pagu (reference) in arranging meeting budgets inside and outside lumajang regency government offices.